Levels of Some Essential Elements in Pregnant Women and Association with Low Birth Weight of Babies in Benin City - Agbonlahor, Osaretin James; Emokpae, Mathias Abiodun (Pakistan journal of nutrition : PJN, 2016)
Poor foetal growth and development has been associated with maternal inadequate or undernutrition. There is no agreement as to whether dietary macro and micro-nutrient supplementation in pregnancy enhance neonatal birth weight. This study evaluates the levels of magnesium, calcium, albumin and phosphorus in pregnant women at delivery, the proportion of the neonates with low birth weight and the relationship between these essential elements and neonatal birth weight. A total of 300 subjects were enrolled, which included 200 healthy pregnant women and 100 age-matched non-pregnant women (controls). The concentrations of essential elements in maternal blood were measured using Atomic Absorption Spectrophotometry and colorimetric methods. The concentrations of magnesium and albumin were significantly (p<0.001) higher in women who had babies with low birth weight than those had normal birth weight. Conversely, calcium (p = 0.002) and phosphorus (p<0.001) levels were significantly lower in women who had babies with low birth weight compared with those that had babies with normal birth weight. The levels of measured variables in the pregnant women at delivery were significantly lower (p<0.001) compared with controls. Supplementation of some of these essential elements may help to prevent the delivery of infants with low birth weight. Therefore measurement of these essential elements may be considered important as part of the routine antenatal investigations.